2017
DOI: 10.1183/20734735.009817
|View full text |Cite
|
Sign up to set email alerts
|

The physiological effects of slow breathing in the healthy human

Abstract: Slow breathing practices have been adopted in the modern world across the globe due to their claimed health benefits. This has piqued the interest of researchers and clinicians who have initiated investigations into the physiological (and psychological) effects of slow breathing techniques and attempted to uncover the underlying mechanisms. The aim of this article is to provide a comprehensive overview of normal respiratory physiology and the documented physiological effects of slow breathing techniques accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
381
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(408 citation statements)
references
References 116 publications
(170 reference statements)
13
381
1
13
Order By: Relevance
“…Furthermore, we found a wide variability in diaphragmatic excursion during both QB and DB, with some healthy subjects showing little or no motion but having no respiratory dysfunction or breathing discomfort. This finding represents a relevant issue: briefly, we could argue that diaphragm motion is a multifactorial ability involving many different mechanisms (such as neuromotor breathing control, muscle fatigability, myocyte metabolic reserve and contractile function, and biomechanics of breathing) and is not simply limited to mechanical and dimensional properties of the rib cage alone [18]. It is known, for example, that subjects with chronic lower back pain and sacroiliac joint pain have abnormal diaphragm movement [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found a wide variability in diaphragmatic excursion during both QB and DB, with some healthy subjects showing little or no motion but having no respiratory dysfunction or breathing discomfort. This finding represents a relevant issue: briefly, we could argue that diaphragm motion is a multifactorial ability involving many different mechanisms (such as neuromotor breathing control, muscle fatigability, myocyte metabolic reserve and contractile function, and biomechanics of breathing) and is not simply limited to mechanical and dimensional properties of the rib cage alone [18]. It is known, for example, that subjects with chronic lower back pain and sacroiliac joint pain have abnormal diaphragm movement [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, deep breathing is a central element for singing, which can impact on both physiological (e.g. cardiovascular and autonomic nervous system) and emotional functions (Busch et al, 2012;Ma et al, 2017;Russo et al, 2017). Further, studies found that group singing can reduce pain threshold and pain perception (Dunbar, Baron, et al, 2012;Dunbar, Kaskatis, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong correlative relationship between respiration rates and autonomic activity, with higher respiration rates stimulating the sympathetic [202] and lower rates stimulating the parasympathetic tone [203]. Research into how controlled slow breathing optimizes homeostatic parameters and promotes health and longevity [203] may reveal integral, vital activities of the unified biological system that is our brain and body.…”
Section: From Embodied Cognition To Embodied Consciousnessmentioning
confidence: 99%
“…Modern lifestyles and goals have been proposed to be behind a widespread and persisting sympathetic over-activation due to an evolutionary mismatch between our predictable, pre-history, tribal lifestyles and the modern hectic lifestyles we live today [208] [209]. By regulating our breathing, we may be able to reduce the ill effects of disrupted sympathovagal balance, enhance poor autonomic reactivity to stress [203], and control otherwise unconscious bodily processes [202] ( Figure 5).…”
Section: From Embodied Cognition To Embodied Consciousnessmentioning
confidence: 99%